2017
DOI: 10.3174/ajnr.a5215
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Survey of the Neuroradiology Work Environment in the United States with Reported Trends in Clinical Work, Nonclinical Work, Perceptions of Trainees, and Burnout Metrics

Abstract: Increasing clinical demands have coincided with destructive effects in the work environment and the ability and desire of neuroradiologists in the United States to perform academic or practice-building duties with a substantial incidence of burnout symptoms. While this survey does not prove causation, the trends and the correlations should be concerning to the leaders of radiology and warrant further monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Within radiology, studies of subspecialty cohorts of radiologists have consistently demonstrated a high prevalence of radiologist burnout. These include musculoskeletal radiologists [10], neuroradiologists [11], pediatric radiologists [12], breast radiologists [13], and cardiothoracic radiologists [14]. These surveys are potentially prone to response bias.…”
Section: Myth 1-burnout Does Not Existmentioning
confidence: 99%
See 1 more Smart Citation
“…Within radiology, studies of subspecialty cohorts of radiologists have consistently demonstrated a high prevalence of radiologist burnout. These include musculoskeletal radiologists [10], neuroradiologists [11], pediatric radiologists [12], breast radiologists [13], and cardiothoracic radiologists [14]. These surveys are potentially prone to response bias.…”
Section: Myth 1-burnout Does Not Existmentioning
confidence: 99%
“…Multiple factors contribute to radiologist burnout, including high workloads, inefficient practice environment, problems with work-life balance, lack of flexibility, reduced autonomy, and loss of meaning at work [10][11][12]32,46]. Effective radiology practice leaders need to genuinely gather input from the radiologists in their practice, making clear that their input is important, and to try to work together to make things better [47].…”
Section: Listen To and Build Teamsmentioning
confidence: 99%
“…Another factor in that study that may have contributed to errors was the lack of other attending colleagues in house for consultations (unpublished data FJL). In 2017, the report of the first workforce survey of US neuroradiologists confirmed that most were reading more cases, working longer hours, and reading more rapidly than they were comfortable with [9].…”
Section: Duty To Patientsmentioning
confidence: 99%
“…Radiology departments are under escalating financial pressure because of declining reimbursements in the past two decades [7,8], and many practices are compelled to increase productivity [9][10][11][12]. Increased clinical demands have been associated with symptoms of burnout, and in a national survey of 432 neuroradiologists, 94.3% reported scaling back in academic activities, which included teaching, mentoring, research, and publications [13]. Not surprisingly, academic productivity, as measured by publications and presentations, has been found to be inversely related to clinical workload (relative value units) at different institutions and radiology subspecialties [14,15].…”
Section: Corporate Medicine Challenges Academic Medicinementioning
confidence: 99%